Faktor Reject Film Radiografi Menggunakan Computed Radiography di RS Bhayangkara Makassar - Harun, Herlinda Mahdania; Musdalifah, Musdalifah; Sumarsono, Sumarsono (Lontara Journal of Health Science and Technology, 2022)
Computed Radiography (CR) is a radiographic system that can convert analog signals into digital signals so that they are easy to process with image processing, to deal with image quality inconsistencies from errors in lighting. This study aims to determine the reject factor of radiographic film using Computed Radiography at Bhayangkara Hospital Makassar. This type of research is quantitative descriptive. The data was collected by means of observation and radiographic interviews. The study was conducted during March-April 2021. The results showed that there were 30 radiographic film rejects. In film processing, there are three factors that cause film rejection, namely human error, tools error, and patient error. The need for accuracy and skill of the radiographer in taking photos so as to reduce film rejects.